PENDEKATAN PERILAKU KOGNITIF DALAM PELATIHAN KETERAMPILAN MENGELOLA KECEMASAN BERBICARA DI DEPAN UMUM - Fatma, Anne; Ernawati, Sri (TALENTA, 2012)
ThisÂ  researchÂ  aimedÂ  toÂ  understandÂ  theÂ  effectivenessÂ  ofÂ  TrainingÂ  onÂ  theÂ  SkillÂ  of ManagingÂ  PublicÂ  SpeakingÂ  AnxietyÂ  UsingÂ  Cognitive-BehavioralÂ  Approach,Â  onÂ  theÂ  wayÂ  it can reduce the level of Public Speaking Anxiety. The experiment design used in this research is Non-randomized Pre-test and Post-testÂ  ControlÂ  GroupÂ  Design,Â  withÂ  theÂ  subjectsÂ  were 20Â  undergraduateÂ  studentsÂ  ofÂ  Sahid University Surakarta experiencing public speaking anxiety. TheÂ  resultÂ  ofÂ  statisticalÂ  analysisÂ  usingÂ  theÂ  Mann-WhitneyâsÂ  testÂ  areÂ  :Â  thereÂ  was significantly different level of public speaking anxiety between the experimental group and control group at pre-test and post-test, with z =Â  -2,374 (p<0,01). The phi square is 0,5388. It means that the training gave 53,88% on reducing the level of public speaking anxiety. The model of Training on the Skill of Managing Public Speaking Anxiety Using Cognitive-BehavioralÂ  ApproachÂ  wasÂ  effectiveÂ  toÂ  reduceÂ  theÂ  levelÂ  ofÂ  publicÂ  speakingÂ  anxiety.Â  So,Â  it was matched with the hypothesis of this research.